Web-Based Online Booking Service System Application Design using Software Development Life Cycle Method - Rinto Diantara; Siswanto Siswanto; Yupianti Yupianti (Jurnal Media Computer Science, 2022)
The purpose of this research is to design a web-based online booking service system application to become a structured booking service data management system. The information obtained will be developed towards computerization through the internet network, which so far is still done conventionally. Data management that can be done by the admin is managing admin data, customer data, booking data, mechanical data, page data and contact data. This application also supports the creation of payment invoices. This web-based online booking service system application has two application interfaces, one for the customer and the other for the administrator. Based on the results of tests carried out both offline and online, this online booking service system application can process booking service data and this application successfully displays information about car services, both booking packages, additional packages, estimated costs and payment invoices. Based on testing using a questionnaire on a web-based online booking service system application, the results obtained are that this application is quite helpful in managing vehicle service booking data and this application can assist the repair shop in providing information related to vehicle service to customers.